THE EFFECT OF CHILDREN LEARNING IN SCIENCE MODEL ON STUDENTS’ LEARNING OUTCOMES - Angreni, Sri Putri; Yurnetti,; Az Zahra, Firda; Yanto, Febri (SEMESTA: Journal of Science Education and Teaching, 2024)
This research was motivated by the low student learning outcomes during the science learning process caused by the application of learning models that are not varied, causing students to be less enthusiastic and tending to be passive in learning. This study aimed the effect of Children Learning In Science (CLIS) learning model on science learning outcomes of seventh-grade students of SMP Negeri 13 Padang. The type of research used is quasi experiment with posttest only control group design. The sampling technique is purposive sampling. Based on the results of the student response questionnaire to the CLIS model, a percentage of 87% was obtained in the very good category. Based on the average of the experimental class of 73.5 and the control class of 66. Then, continued with the hypothesis test using the t-test, the tcount> ttable value is 3.85 > 2,00 with a sample of 32 students and α=0.05. The results of the hypothesis are H0 rejected and Ha accepted, meaning that there is a significant effect of the application of the Children Learning In Science (CLIS) learning model on the learning outcomes in class VII SMPN 13 Padang.